2016
DOI: 10.1037/dev0000143
|View full text |Cite
|
Sign up to set email alerts
|

Observed sensitivity during family interactions and cumulative risk: A study of multiple dyads per family.

Abstract: The present study sought to investigate the family, individual, and dyad-specific contributions to observed cognitive sensitivity during family interactions. Moreover, the influence of cumulative risk on sensitivity at the aforementioned levels of the family was examined. Mothers and 2 children per family were observed interacting in a round robin design (i.e., mother-older sibling, mother younger-sibling and sibling-dyad, N ϭ 385 families). Data were dyadic, in that there were 2 directional scores per interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 59 publications
5
24
3
Order By: Relevance
“…Second, adding to recent findings regarding mentalization and family interactions (Jessee et al., ; Marcu et al., ), our findings suggest that under low contextual stress, a mother's spontaneous ability to understand her infants' mental states contributes not only to the quality of the mother–infant relationship but also to the quality of the family interaction as a whole. In line with previous studies, our results also indicated that mothers under high CSC risk were less sensitive than mothers under low CSC (e.g., Browne et al., ; Neuhauser, ; Smaling, Huijbregts, Suurland, et al., ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Second, adding to recent findings regarding mentalization and family interactions (Jessee et al., ; Marcu et al., ), our findings suggest that under low contextual stress, a mother's spontaneous ability to understand her infants' mental states contributes not only to the quality of the mother–infant relationship but also to the quality of the family interaction as a whole. In line with previous studies, our results also indicated that mothers under high CSC risk were less sensitive than mothers under low CSC (e.g., Browne et al., ; Neuhauser, ; Smaling, Huijbregts, Suurland, et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…It is well accepted that risk has a cumulative effect, such that the presence of several risk factors amplifies their negative effect on child development (e.g., Atzaba-Poria, Pike, & DeaterDeckard, 2004;Evans, Li, & Whipple, 2013) as well as on the family system (Browne, Leckie, Prime, Perlman, & Jenkins, 2016;Browne, Plamondon, Prime, Puente-Duran, & Wade, 2015). Importantly, cumulative risk has been found to be negatively associated with maternal sensitivity, involving distal environment and child-driven stress risk factors (Browne et al, 2016;Neuhauser, 2016;Smaling, Huijbregts, Suurland, et al, 2016). Furthermore, previous research has shown that environmentalfamilial risk among mothers of preterm infants predicted continuation of maternal emotional distress from birth to 24 months, suggesting that the combination of prematurity together with other environment-driven stressors may be associated with chronic stress (Poehlmann, Schwichtenberg, Bolt, & Dilworth-Bart, 2009).…”
Section: Cumulative Stressful Context (Csc) Riskmentioning
confidence: 99%
“…It is also notable that economic hardship does not operate on its own. SES clusters risk [60] such that children are exposed to multiple challenges that compromise development (e.g., maternal depression, unemployment, domestic violence, poor neighborhoods) and parenting [61].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, a multilevel approach may be used instead (Jenkins et al, 2012 ; Nestler, 2016 ). While the latter approach can more easily deal with varying family sizes (Browne et al, 2016 ), the former has been more commonly used by family researchers.…”
Section: Srm Population Parametersmentioning
confidence: 99%